Peningkatan Hasil Belajar Pendidikan Agama Katolik dengan Model PBL Berbantuan Wordwall Game Kelas V SDN 26 Simanindo Sangkal - Melda Malau; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This classroom action research aims to improve the learning outcomes of Catholic Religious Education among fifth-grade students at SDN 26 Simanindo Sangkal using the Problem-Based Learning (PBL) model supported by the Wordwall Game as an interactive media. The research was conducted in two cycles, with each cycle involving stages of planning, action, observation, and reflection. The primary focus was on assessing students' cognitive learning outcomes and critical thinking skills, aligned with the Pancasila Student Profile. The results of the research demonstrated a significant improvement in student performance. In the first cycle, the average cognitive score was 80.71, which increased to 91.43 in the second cycle. Additionally, students showed increased engagement in asking relevant questions, identifying key information from various sources, and formulating conclusions, which are critical elements of critical thinking. The use of the Wordwall Game successfully enhanced the learning process by making it more interactive and motivating for students. In conclusion, the implementation of the PBL model with the assistance of the Wordwall Game proved to be effective in enhancing both the cognitive learning outcomes and the critical thinking skills of students in Catholic Religious Education.